Digital PCR improves the quantitation of DMR and the selection of CML candidates to TKIs discontinuation. (4th April 2019) - Bernardi, Simona; Malagola, Michele; Zanaglio, Camilla; Polverelli, Nicola; Dereli Eke, Elif; D'Adda, Mariella; Farina, Mirko; Bucelli, Cristina; Scaffidi, Luigi; Toffoletti, Eleonora; Deambrogi, Clara; Stagno, Fabio; et al.
Abstract: Treatment‐free remission (TFR) by tyrosine kinase inhibitors (TKI) discontinuation in patients with deep molecular response (DMR) is a paramount goal in the current chronic myeloid leukemia (CML) therapeutic strategy. The best DMR level by real‐time quantitative PCR (RT‐qPCR) for TKI discontinuation is still a matter of debate. To compare the accuracy of digital PCR (dPCR) and RT‐qPCR for BCR‐ABL1 transcript levels detection, 142 CML patients were monitored for a median time of 24 months. Digital PCR detected BCR‐ABL1 transcripts in the RT‐qPCR undetectable cases. The dPCR analysis of the samples, grouped by the MR classes, revealed a significant difference between MR 4.0 and MR 4.5 ( P = 0.0104) or MR 5.0 ( P = 0.0032). The clinical and hematological characteristics of the patients grouped according to DMR classes (MR 4.0 vs MR 4.5‐5.0 ) were superimposable. Conversely, patients with dPCR values <0.468 BCR‐ABL1 copies/µL (as we previously described) showed a longer DMR duration ( P = 0.0220) and mainly belonged to MR 4.5‐5.0 ( P = 0.0442) classes compared to patients with higher dPCR values. Among the 142 patients, 111 (78%) discontinued the TKI treatment; among the 111 patients, 24 (22%) lost the MR 3.0 or MR 4.0 . RT‐qPCR was not able to discriminate patients with higher risk of MR loss after discontinuation ( P = 0.8100). On the contrary, according to dPCR, 12/25 (48%) patients with BCR‐ABL1 values ≥0.468 and 12/86 (14%) patients with BCR‐ABL1 values <0.468 lost DMR in this cohort, respectively ( P = 0.0003). Treatment‐free remission of patients who discontinued TKI with a dPCR <0.468 was significantly higher compared to patients with dPCR ≥ 0.468 (TFR at 2 years 83% vs 52% P = 0.0017, respectively). In conclusion, dPCR resulted in an improved recognition of stable DMR and of candidates to TKI discontinuation. Abstract : In this study, we compared the accuracy of digital PCR (dPCR) and RT‐qPCR for BCR‐ABL1 transcript levels detection by monitoring 142 CML patients for a median time of 24 months. The clinical and hematological characteristics of the patients grouped according to DMR classes (MR 4.0 vs MR 4.5‐5.0 ) were superimposable, while patients with dPCR values <0.468 BCR‐ABL1 copies/µL (as we previously described) showed a longer DMR duration ( P = 0.02) and mainly belonged to MR 4.5‐5.0 ( P = 0.044) classes compared to patients with higher dPCR values. Among the 142 patients, 111 (78%) discontinued the TKI treatment and 24 (22%) among the 111 patients lost the MR 3.0 or MR 4.0 : according to dPCR, 12/25 (48%) and 12/86 (14%) had BCR‐ABL1 values ≥0.468 and <0.468, respectively ( P = 0.0003); on the contrary, RT‐qPCR was not able to discriminate patients with higher risk of MR loss after discontinuation ( P = 0.81). In conclusion, dPCR resulted in an improved recognition of stable DMR and of candidates to TKI discontinuation.